EVALUATION OF JAPANESE LANGUAGE WRITING CLASS: INTEGRATING JAPAN FOUNDATION STANDARD WITH THE VISION OF THE UNIVERSITY IN A LECTURE’S LEARNING OBJECTIVE - Setiawati, Ai Sumirah; Supriatnaningsih, Rina; Nurhayati, Silvia; Rosliyah, Yuyun; Elmubarok, Zaim (International Journal of Psychosocial Rehabilitation, 2020)
Universitas Negeri Semarang, as a conservation-oriented university, has been using a curriculum that implements conservative values in its lecture sessions. For instance, Sakubun Schochukyu subject (elementary-level writing skill) adds conservative values-related objective (culture, environment, and character) in its learning syllabus. The evaluation of the lecturing process has only been carried out during tests or when giving assignments to the students. However, a learning course is supposed to be evaluated by referring to several factors to define its success. Therefore, the Sakubun Schochukyu lecturing process is evaluated based on self-assessment, students’ perception, and writing assessment. This study reported that students’ selfassessment highly contributed to the learning objective. The students also responded positively to the Sakubun Shochukyu lecture. In addition, students’ writing ability fell under a “very good” category with the score ranging from 81-85. Nevertheless, the element of grammar still needed improvement since there were some grammatical and expression errors that occurred in the writing, yet the overall meaning were still understandable.